INTEGRATING TOPIC TYPE STRATEGY TO INCREASE VOCATIONAL HIGHER EDUCATION STUDENTS WRITING SKILL - Siska Amelia Maldin (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2022)
Teaching English in Vocational Higher Education are designed not only to achieve students’ competence in obtaining English for academic matters but also to achieve skilled aspect for preparing learners in the industrial field, especially in writing skill. Thus, effective strategies should be delivered to achieve the goals of gaining students’ competence in writing skills. One of the strategies implemented is topic types which are expected to enhance students writing skills. This study is designed by using the library research method, which claimed that this topic types strategy might encourage students to generate ideas especially to help them in managing ideas before writing.